Genetic structure and phylogeography of a European flagship species, the white‐tailed sea eagle Haliaeetus albicilla. (17th December 2012) - Langguth, Tobias; Honnen, Ann‐Christin; Hailer, Frank; Mizera, Tadeusz; Skoric, Stefan; Väli, Ülo; Zachos, Frank E.
<x xml:space="preserve">Abstract</x> We analysed 120 white‐tailed sea eagles Haliaeetus albicilla from eastern (Poland and Estonia) and southeastern (Serbian Danube population) Europe for genetic variability and structuring at the mitochondrial control region and seven nuclear microsatellite loci. We combined this new dataset with sequence and genotype data from previous analyses covering Greenland and Eurasia (total sample sizes of 420 and 186 individuals for mtDNA and microsatellites, respectively) to address the following questions: 1) does the large eastern population in Europe add significantly to the species' overall genetic diversity? 2) Do the new sequence data match the clinal distribution pattern (west to east) of the two major mtDNA lineages? 3) Does the preliminary hypothesis of two nuclear genetic clusters recently found in this species hold for the whole of Europe, and do these clusters show a geographic pattern? Our results confirmed Europe as a stronghold of genetic diversity in white‐tailed sea eagles, and the east of the continent contributed disproportionately to this, the reason being the admixture of eagles with different genetic background. As hypothesised, both mitochondrial lineages were recovered also in eastern Europe, but the globally more eastern lineage was dominant. The presence of two microsatellite clusters was also confirmed, and these groups, too, show a non‐random geographic distribution, with, except for Poland, a high proportion of 'eastern‐type' eagles in the populations of east–central and eastern Europe.